Historical Roots and Seminal Papers of Quantum Technology 2.0. - Scheidsteger, Thomas; Haunschild, Robin; Ettl, Christoph (NanoEthics, 2022)
We present a historical study of Quantum Technology 2.0 using more than 66,000 papers from 1980 to 2020 that had been assigned to four subfields. We applied the method reference publication year spectroscopy to respective publication sets of the subfields in order to identify their historical roots and seminal papers. We found 126 of them in total, 43 in quantum metrology and sensing, 46 in quantum communication and cryptography, 42 in quantum computing, and 33 in quantum information science–with a significant overlap between subfields–which are all discussed in their relevance for the respective subfield. We compared the subfields regarding their interrelationship and distinctiveness in terms of their most influential papers and were able to deduce a common core set of five seminal publications in all four subfields.